Cloning, phylogenetic research, and prokaryotic expression study of the metabolic detoxification gene EoGSTs1 in Empoasca onukii Matsuda - Zhang,Yujie; Chen,Wenlong; Li,Ming; Yang,Lin; Chen,Xiangsheng (PeerJ, 2019)
Due to the misuse of chemical pesticides, small green leafhoppers (Empoasca onukii Matsuda) have developed resistance to pesticides, thereby posing a serious problem to the tea industry. Glutathione S-transferases (GSTs) are an important family of enzymes that are involved in pesticide resistance in Empoasca onukii Matsuda. Empoasca onukii GST sigma 1 (EoGSTs1, GenBank: MK443501) is a member of the GST family. In this study, the full-length cDNA of EoGSTs1 was cloned by reverse transcription polymerase chain reaction (qPCR), and its taxonomic identity was examined. Furthermore, we performed bioinformatics and phylogenetic analyses of the gene and structural and functional domain prediction of the protein. The results demonstrate that EoGSTS1 belongs to the Sigma family of GSTs; the full-length EoGSTs1 cDNA is 841 bp with a 624-bp coding region that encodes a 23.68932-kDa protein containing 207 amino acids. The theoretical isoelectric point (IEP) was calculated to be 6.00. Phylogenetic analysis indicates that EoGSTS1 is closely related to the Sub psaltriayangi subfamily of the Cicadoidea superfamily in order Hemiptera, whereas it is distantly related to Periplaneta americana of order Blattodea. Amino acid sequence alignment of EoGSTS1 and GSTs from four other insects of order Hemiptera revealed protein sequence conservation. Tertiary structure analysis and structural domain functional predictions of the protein revealed that EoGSTS1 contains nine α helices and two β sheets with one conserved GST domain. The results of enzyme activity assay showed that recombinant EoGSTs1 (rEoGSTs1) protein had catalytic activity for substrate 1-chloro-2,4-dinitrobenzene (CDNB) and exhibited the highest activity at pH 7 and 25 °C. The Michaelis constant Km of rEoGSTs1 protein was 0.07782 ± 0.01990 mmol/L, and the maximum reaction rate Vmax was 12.15 ± 1.673 µmol/min⋅mg. Our study clarified the taxonomic identity of small green leafhopper EoGSTs1 and revealed some properties of the gene and its encoded protein sequence. According to the catalytic activity of the rEoGSTs1 enzyme on the model substrate CDNB, we infer that it functions in the degradation of exogenous substances.
Keywords: Clone; Phylogenetic analysis; Empoasca onukii; EoGSTs1; Bioinformatics; Prokaryotic expression